The Effect of Surface Functionalization on the Immobilization of Gold Nanoparticles on Graphene Sheets - Min Song; Juan Xu; Changzi Wu (Journal of Nanotechnology)
In our study, graphene oxide is synthesized by Hummers method. And then, carboxylic acid functionalized graphene (graphene-COOH), thiol-functionalized graphene (graphene-SH), and highly dispersive graphene are prepared by chemical modification of respective groups on the graphene surface. Furthermore, we explore a solution-based approach to prepare three differently functionalized graphene-gold composites by one-step chemical reduction of AuCl4 - ions in respective functionalized graphene suspensions, where the gold nanoparticles are deposited on the functionalized graphene surface during their synthesis process. In addition, we compare the influence of surface functionalization on the growth of gold nanoparticles on graphene surface. Transmission electron morphology (TEM) and ultraviolet-visible (UV-Vis) spectroscopy are employed to study the effect of surface functionalities on AuNPs distribution onto the graphene surface and demonstrate the successful immobilization of AuNPs on graphene surface.